2021
DOI: 10.1007/s00125-020-05351-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital discharge and mortality in patients with diabetes and COVID-19: updated results from the nationwide CORONADO study

Abstract: Aims/hypothesis This is an update of the results from the previous report of the CORONADO (Coronavirus SARS-CoV-2 and Diabetes Outcomes) study, which aims to describe the outcomes and prognostic factors in patients with diabetes hospitalised for coronavirus disease-2019 (COVID-19). Methods The CORONADO initiative is a French nationwide multicentre study of patients with diabetes hospitalised for COVID-19 with a 28-day follow-up. The patients were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
6
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(210 citation statements)
references
References 32 publications
13
184
6
7
Order By: Relevance
“… [15] Updated results from the French CORONADO Study of 2796 PLWD (mean age 69·7) who were hospitalised reported a mortality rate of 11·2% within 7 days, which continued to increase to 20·6% by 28 days. [16] We can only speculate about factors that account for such a high mortality in our setting, even in relatively young patients, which includes social determinants such as poor access to care, general poor standards of chronic care for diabetes such as glycaemic control and management of complications, higher threshold for admission and reduced access to ICU beds once admitted. [17] The high background of infectious diseases in the population may also contribute to mortality.…”
Section: Discussionmentioning
confidence: 95%
“… [15] Updated results from the French CORONADO Study of 2796 PLWD (mean age 69·7) who were hospitalised reported a mortality rate of 11·2% within 7 days, which continued to increase to 20·6% by 28 days. [16] We can only speculate about factors that account for such a high mortality in our setting, even in relatively young patients, which includes social determinants such as poor access to care, general poor standards of chronic care for diabetes such as glycaemic control and management of complications, higher threshold for admission and reduced access to ICU beds once admitted. [17] The high background of infectious diseases in the population may also contribute to mortality.…”
Section: Discussionmentioning
confidence: 95%
“…A similar result was reported by Izzi-Engbeaya for deaths within 30 days (OR 0.66; 95% CI, 0.30–1.52) in univariate analysis [ 24 ] and by Silverii and colleagues [ 25 ]. The Coronavirus SARS-CoV-2 and Diabetes Outcomes (CORONADO) study also found a neutral effect of SUs/glinides on mortality (OR 0.83; 95% CI, 0.67–1.03) within 28 days [ 26 ]. In a nationwide observational cohort study done with data from the National Diabetes Audit for people with type 2 diabetes, Khunti and colleagues have reported that the use of SUs marginally but significantly reduced COVID-19 mortality whereas this was not observed for glinides [ 19 ].…”
Section: Sulphonylureasmentioning
confidence: 99%
“…In light of these experimental premises, GLP-1RA could be considered an ideal drug to counteract the pro-inflammatory cytokine response after severe COVID-19 infection. Five retrospective studies are available on the effect of GLP-1RA on COVID-19-related mortality [ 19 , 25 , 26 , 39 , 49 ]. None of these show that the use of GLP-1 before SARS-CoV-2 infection could potentially interfere with the disease's course.…”
Section: Glucagon-like Peptide 1 Receptor Agonists (Glp-1ra)mentioning
confidence: 99%
“…However, our results suggested that some of these therapies could alter COVID-19 outcomes differently in women and men. Thus, the reduced risk of death associated with metformin use, already reported in the whole CORONADO population (28,39), was only observed in men. This contrasts with a recent retrospective study suggesting that metformin is associated with better survival specifically in women (40).…”
Section: Discussionmentioning
confidence: 79%